Effects of detyrosinated tubulin on Na+,K+-ATPase activity and erythrocyte function in hypertensive subjects - Amaiden, Marina R.; Santander, Verónica S.; Monesterolo, Noelia E.; Nigra, Ayelen D.; Rivelli, Juan F.; Campetelli, Alexis N.; Pie, Juan; Casale, Cesar H. (FEBS letters, 2015)
•Detyrosinated tubulin is able to inhibit the NKA activity.•Erythrocytes of hypertensive subjects have a reduced content and activity of TTL.•GluTub levels and NKA activity are related to erythrocyte deformability.•The mechanism explains involvement of tubulin in hypertension. Formation of tubulin/Na+,K+-ATPase (NKA) complex in erythrocytes of hypertensive subjects results in a 50% reduction in NKA activity. We demonstrate here that detyrosinated tubulin, which is increased in hypertensive erythrocytes membranes, enhances the inhibitory effect of acetylated tubulin on NKA activity. Moreover, we report a reduced content and activity of the enzyme tubulin tyrosine ligase in erythrocytes of hypertensive subjects. Such alterations are related to changes in erythrocyte deformability. Our findings indicate that the detyrosination/tyrosination cycle of tubulin is important in regulation of NKA activity, and that abnormalities in this cycle are involved in hypertension development.